Geophysical exploration methods on bauxite reservoirs in L gasfield, Ordos Basin - Yu, Qi; Dan, Li; Shanshan, Yu; Qixin, Li (Frontiers in Energy Research, 2023)
Introduction: The L gasfield on the eastern edge of the Ordos Basin mainly focuses on the exploration and development of coalbed methane and tight sandstone gas. As the overlying strata of Majiagou Formation of Lower Ordovician in Lower Paleozoic, bauxite has always been considered a regional cap rock and has not been widely followed with interest. The drilled wells has revealed that bauxite can be used as a unconventional reservoir with good reservoir properties. In the future, it will become a new natural gas exploration target in the L region. This article is dedicated to the comprehensive study of geophysical methods for the bauxite exploration in the L region. Methods: Firstly, we use seismic data to restore paleo-geomorphology of the Lower Paleozoic. Secondly, we analyze the well log data of different paleo-geomorphic unit. Then, we establish a mineral model based on the logging data to calculate the lithological composition and porosity, and use imaging logging to evaluate the pore structure and fluid type. Result and Discussion: Finally, we obtained favorable reservoir development zones for bauxite, guiding exploration and evaluation of bauxite.